Islamic Education in Egypt: An Overview, System Structure, and Government Policies - Suhaili, Hidayati; Zalnur, Muhammad; Rosyada, Dede; Kirin, Arwansyah Bin; Nini, Nini; Sartini, Titi (STAI Publisistik Thawalib Jakarta, 2025)
Al-Azhar University, Egypt, presents a model of Islamic education that is moderate and holistic, relevant in addressing the challenges of modernity, radicalism, and the integration of Islamic tradition with scientific progress. This study identifies a gap in the previous literature, which generally partially discusses Islamic education in Egypt, focusing on the history of Al-Azhar or primary education, without comprehensively analysing the integration of traditional and modern values, system structure, and state policies. This study employs a qualitative approach, utilising data collection techniques through literature review and document analysis of scholarly journals, academic books, and official reports from the Ministry of Education and Al-Azhar University. Data analysis is conducted using qualitative content analysis methods, which include stages of collection, filtering, coding, categorisation, synthesis, and triangulation. The results show that the Islamic education system in Egypt has successfully integrated religious and general knowledge through a moderate and inclusive curriculum, supported by government policies such as the Al-Azhar Law of 1961 and the 2014 curriculum reform. However, educational access inequality, limited technological infrastructure, and conservative resistance continue to hinder comprehensive reform efforts. In conclusion, these findings offer important lessons for developing Islamic education in Indonesia and other Muslim countries.